Developing integrated control systems media to enhance the electrification competency of electric railway drives - Rizqi Ervani; Istanto Wahyu Djatmiko (Jurnal Pendidikan Vokasi, 2024)
This study aimed to develop and evaluate integrated control systems media for the traction system of electric railway drives to enhance students’ electrification competencies. Specifically, the study sought to analyze the operation, assess the feasibility, and produce effective instructional media for use in the Railway Electrical Engineering program at Madiun State Polytechnic. A development research design was employed by combining the RAD (Rapid Application Development) and ASSURE models. The subjects were 39 railway students, and data were collected through observations, interviews, questionnaires, and tests. Instrument validation was conducted using Aiken’s V and Pearson Product Moment correlation, while reliability was tested with Cronbach’s Alpha. Data were analyzed using Huberman’s steps for qualitative findings and descriptive statistics, Wilcoxon test, and Gain Score analysis for quantitative data. The results indicate that the developed traction system media—consisting of an application and teaching modules—were rated “Very Feasible” by experts and students. Statistical tests showed significant improvements in the electrification competencies of the experimental group compared to the control group. The integrated control systems media not only support effective laboratory practice but also foster interactive and engaging learning experiences. This study contributes to vocational education by demonstrating how technology-based instructional media can strengthen students’ technical competencies in railway electrification and by providing a model that can be replicated in other polytechnic and technical training contexts.